Motives for Employees Communicate Positive Electronic Word of Mouth (eWOM) on Social Network Sites: Exploring Moderating Mechanisms. Issue 1 (February 2022) - Zhang, Ya; Zhang, Jing; Liu, Chengchen
Electronic word of mouth (eWOM) has received attention from marketing academic society in the last decade. Extant literature explains why consumers spread eWOM in social network sites (SNS), but the motivations of internal employees' eWOM behavior are not extensively researched. This article aims to explore what factors motivate employees to create positive eWOM in SNS and the moderating variables in the effects of these motivations. Capturing motivations of employees' positive eWOM behavior in SNS and moderating variables, the hypotheses were proposed by drawing on the literature of organizational citizenship behavior (OCB), internal marketing, and consumer eWOM. Responses from a sample of 301 employees were conducted through an online questionnaire survey. The result reveals three job-related motivations and two social-related motivations of employees' positive eWOM behavior with four moderating variables influencing these relationships in different ways. This study makes theoretical contributions to eWOM literature by integrating consumers' eWOM and employees' OCB research, probing into this issue from the internal employees' perspective. Besides, it provides insightful implications for marketing managers on motivating employees to create positive eWOM in SNS voluntarily.